Chapter Coralligenous cliffs in Tuscany: distribution, extension of the habitat and structure of assemblage - Cecchi, Enrico (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The present study aims at assessing the distribution and extension of the coralligenous cliffs in Tuscany and describing the structure and the patterns of spatial variability. The mapping of seabed was obtained through Multibeam echosounder data coupled with video images. Coralligenous cliffs were sampled by SCUBA divers in 11 sectors of rocky costs following the STAR procedure. Coralligenous cliffs were present in all study sites, with a total length of about 62.5 km and a total surface of 0.47 km2. The linear extension of the habitat may be estimated about the 20% of Tuscany rocky coast.